Effects of life expectancy on economic growth: New results using the flexible Box-Cox power transformation model - Albert Okunade; Ahmad Osmani (Applied Economics Letters, 2020)
This article revisits the effects of life expectancy (LE) on economic growth (IPC) reported in previous research. Maximum likelihhod (ML) estimates are obtained based on the monotonic nonlinear flexible Box-Cox power transformation regression model. This variance stabilizing model, unlike the a priori restrictive nested log and linear forms, is a parametrically richer flexible functional form for transforming the dependent and independent variables separately with different power parameters. The conditional life expectancy elasticity of income estimates are found to vary across fitted models and the more robust flexible Box-Cox power model outperforms the restrictive linear and log specifications fitted in past work. Contrary to past findings indicating large negative and highly elastic (statistically significant) life expectancy (LE) elasticity of income (INC), new results from the preferred fully flexible Box-Cox model incorporating the nonlinear effect yield a much smaller negative (statistically significant) and inelastic life expectancy elasticity of income estimate. Study explores some policy options for enhancing economic growth during periods of high or rising life expectancy.
Additional information: This is the pre-print of the published article. Refer to the Applied Economics Letters for the published version of this work.
Keywords: I1; O1; 330; flexible Box-Cox transformation; non-linearity; economic growth; elasticity